2008
DOI: 10.1242/jeb.007658
|View full text |Cite
|
Sign up to set email alerts
|

Elasticity, unexpected contractility and the identification of actin and myosin in lobster arteries

Abstract: SUMMARY

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
7

Year Published

2010
2010
2016
2016

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 32 publications
(46 reference statements)
0
12
0
7
Order By: Relevance
“…Several of these same modulators, including proctolin (Wilkens et al, 2005), and a number of different FMRFamide-like peptides (Fort et al, 2007a;Stevens et al, 2009;Wilkens et al, 2005), also exert effects at the neuromuscular junction or directly on crustacean cardiac muscle. Some have likewise been shown to affect other aspects of the circulatory system, including blood vessels and vascular resistance (Wilkens et al, 2008;Wilkens and Taylor, 2003). Moreover, several recent studies have shown that the effects of the same modulator differ either quantitatively or qualitatively when applied to the semi-intact heart and the isolated CG (Fort et al, 2004;Fort et al, 2007a;Fort et al, 2007b;Stevens et al, 2008;Stevens et al, 2009), suggesting the possibility that these modulators exert effects at other sites, potentially including feedback pathways within the cardiac neuromuscular system.…”
Section: Discussionmentioning
confidence: 99%
“…Several of these same modulators, including proctolin (Wilkens et al, 2005), and a number of different FMRFamide-like peptides (Fort et al, 2007a;Stevens et al, 2009;Wilkens et al, 2005), also exert effects at the neuromuscular junction or directly on crustacean cardiac muscle. Some have likewise been shown to affect other aspects of the circulatory system, including blood vessels and vascular resistance (Wilkens et al, 2008;Wilkens and Taylor, 2003). Moreover, several recent studies have shown that the effects of the same modulator differ either quantitatively or qualitatively when applied to the semi-intact heart and the isolated CG (Fort et al, 2004;Fort et al, 2007a;Fort et al, 2007b;Stevens et al, 2008;Stevens et al, 2009), suggesting the possibility that these modulators exert effects at other sites, potentially including feedback pathways within the cardiac neuromuscular system.…”
Section: Discussionmentioning
confidence: 99%
“…Other arteries respond to proctolin with slow circumferential, but not longitudinal, contractions. The magnitude of these contractions appears sufficient to account for the measured increases in vascular resistance [220].…”
Section: Effects On Cardiac Musclementioning
confidence: 91%
“…The decapods have received by far the most extensive investigation, and here, proctolin has been shown to modulate exoskeletal muscles/neuromuscular junctions [213][214][215][216], the cardiac neuromuscular system [98, [217][218][219][220][221][222], the stomatogastric neuromuscular system [92, 103, 204, 223-228], the ventilatory system [229], the neural circuitry controlling the swimmerets [230,231], mechanosensory neurons [232][233][234], and hindgut contractility [235]. In non-decapods, proctolin has been shown to be a potent myomodulator [236,237] and to modulate cardiac output [238].…”
Section: Pigment Dispersing Hormonementioning
confidence: 99%
See 1 more Smart Citation
“…Redistribution of arterial flow is accomplished by muscular cardioarterial valves located at the entrance to each arterial system (Maynard, 1960) and has been demonstrated in several species [in Bathynomus: by Kihara and Kuwasawa (Kihara and Kuwasawa, 1984); in Cancer magister: by McGaw and colleagues (McGaw et al, 1994); in Panulirus japonicas: by Kuramoto and Ebara (Kuramoto and Ebara, 1984); and in Procambarus clarkii: by Reiber (Reiber, 1994)]. Beyond the cardio-arterial valves, the vasculature has been shown to contain some contractile elements, yet the functional significance of this has yet to be determined (Shadwick et al, 1990;Wilkens, 1997;Wilkens and Taylor, 2003;Wilkens et al, 2008). One exception, the posterior aorta of the abdomen, contains muscle bands in its lateral walls and also has valves along its length, located at each of the branching segmental lateral vessels, that might allow for changes in resistance Wilkens and Taylor, 2003).…”
Section: Introductionmentioning
confidence: 99%